Best therapeutic practices in the management of obstetric sepsis - Gabriel Petre Gorecki; Oana Denisa Balalau; Diana Elena Comandasu; Anca Daniela Stanescu; Dana Rodica Tomescu (Journal of Mind and Medical Sciences)
Background. Physiological changes that occur during pregnancy make maternal sepsis a difficult condition to diagnose and treat, still having a fairly high mortality rate. Consequently, an early diagnosis and prompt therapeutic management of sepsis can significantly decrease mortality. The purpose of this study is to review literature data that present current practices in the management of obstetric sepsis. Methods. To collect the data required for the study, we performed a search of published articles in the PubMed and Google Scholar databases related to obstetric sepsis. Research paper articles from the period 2012-2022 were included in the analysis. In addition, 145 articles from the period 2012-2022 were evaluated, with the aim of finding out in which situations the risk of maternal death is higher. Thus, the analysis included a total number of 151 articles, which were divided into two distinct stages. Results. The risk of maternal death is higher among patients with the human immunodeficiency virus (HIV), followed by Escherichia coli, genital tract infection, cancer, drug users and in the case of patients with chronic liver disease. Conclusions. After analyzing the data, we found that prompt and focused antibiotic therapy as well as fluid resuscitation are essential to increase the chances of survival of these patients.